Possibilities of the Performing Arts Archive: Survivals Behind and in Front of the Curtain - Bifaretti, María Eugenia (2023)
This text aims to problematize the possible ways of archiving and historicizing performing practices. For this purpose, it approaches the art works TODO, la imposibilidad de vaciar (2019) and TODO Performance (2021), directed by the performing artist Laura Valencia (La Plata, Argentina), where the collection of stage objects that the director has used and treasured during twenty-five years are activated. From a critical perspective of history (Scott, 2001) and affects (Ahmed, 2015), the artist's experience is taken as the main source and reflects on the power of art as an archive (Guasch, 2005), the idea of poetics of the rest (López, 2018), and the anachronistic images (Didi-Huberman, 2011) that are suggested on stage to consider those scenic objects as objects-remains and their uses in the works as memory exercises. Therefore, the idea of performing arts archive as repertoire of survivals is proposed in order to think what other ways of archiving enable these objects-rests and their bodily and affective dimensions, as well as the implications of addressing singular experiences for the historicization of stage events.